Climatic Changes and Psychiatric Disorders - Kader Semra Karataş; Sevda Ocak (Van Tıp Dergisi, 2018)
Although recognition of seasonal influences on psychiatric disorders lie down old times, documentation of seasonal influences is not more than two decades old. The imbalance of meteorological factors, such as mean temperature, day light duration, humidity, atmospheric pressure can creates many disorders in the normal life of sensetive people. The most common reaction to changing weather conditions could have seen as a psychological, emotional or behavioral character and seen as many psychiatric disorders or increases incidence of the psychiatric diseases. While many studies have focused on the impact of seasonality at bipolar and related disorders there have a little knowledge about other psychiatric disorders such as schizophrenia, sleep disorders, anxiety disorders. Same brain regions, neuronal phasic firing, neuronal transmission, presinaptic / postsinaptic neurotransmitter's level changes can be affected similiar way by climatic changes, psychological status, psychiatric diseases. Several researcher have studied different affect of climatic factors to susceptible people and/or people who have psychiatric diseases but seasonality is still unclear in those population. In this literature we have reviewed association amoung meteorological factors, like temperature, day light duration, humidity, atmospheric pressure, psychological states and psychiatric disorders by searching medline, pubmed, science direct literature scanning.